Constraints of Green Buildings in Iraqi Cities - Ismaeel, Nabil Taha; Hussain, AbdulHussain Ali (Iraqi Journal of Architecture and Planning, 2019)
The construction and buildings sector are one of the most energy-consuming sectors, accounting for one-third of the world’s total energy consumption and one-third of the world’s CO2 emissions, this leads to environmental, health and psychological damages for humans and society, with an increase in other urban problems in city. This is result of reliance on fossil fuels, construction materials and excessive consumption of natural resources that cause an increase in greenhouse gas emissions. Concept of green buildings has emerged with sustainable trends in fields of architecture and urban planning. It is considered an integrated architecture with environment and nature. It reduces pollution rate to 1/6 of world’s CO2 emissions. It provides a safe, comfortable and healthy environment for human and reduces the consumption and preservation of natural resources, for future generations by recycling waste, wastewater, roofs and green facades, and use of suitable building materials with the environment, as well as integrated design with buildings and urban context in terms of formation and direction of buildings and use of sustainable building materials and use of renewable energy and others. The climate in Iraq, especially in summer, is characterized by high temperatures. It is more than 50 Â°c, with winter temperatures dropping and uneven significantly between summer and winter, so we need buildings that consider the requirements of human thermal comfort, reduce energy consumption and natural resources, and provide a healthy and psychological environment, to reduces emissions harmful to environment. There are many obstacles to establishment of green buildings in Iraqi cities, most important of which are laws and legislation that require its legislation to suit technological advances in architecture, as well as technical, and social constraints and others.